The artful species aesthetics, art, and evolution - Davies, Stephen, 1950- (Oxford : Oxford University Press, 2013)
Stephen Davies explores the idea that art, and our aesthetic sensibilities more generally, should be understood as an element in human evolution. He asks: Do animals have aesthetics? Do our aesthetic preferences have prehistoric roots? Is art universal? What is the biological role of aesthetic and artistic behaviour?
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on Nov. 13, 2012).
Keywords: Aesthetics; Human evolution; Art -- Psychological aspects